Meta-analysis of the use of hyaluronic acid gel to prevent intrauterine adhesions after miscarriage. (January 2020) - Fei, Zheng; Xin, Xin; Fei, He; Yuechong, Cui
Abstract: Background: Intrauterine adhesions are a severe complication after miscarriage. Hyaluronic acid gel has been used to prevent intrauterine adhesions after miscarriage. Objective: To systematically evaluate the efficacy of adjuvant therapy with hyaluronic acid gel to prevent intrauterine adhesions after miscarriage. Search strategy: The Cochrane Library, Embase and PubMed databases were searched for articles published before 31 July 2018 using the terms: ('hyaluronic acid gel' or 'gel') and ('dilatation and curettage' or 'D&C' or 'abortion' or 'miscarriage' or 'hysteroscopic') and ('intrauterine adhesions' or 'Asherman syndrome' or 'IUA' or 'endometrial injury' or 'intrauterine adhesion'). Selection criteria: Randomized controlled trials of hyaluronic acid gel therapy after miscarriage. Data collection and analysis: Four studies were included in the meta-analysis (625 patients in total). Dichotomous outcomes were expressed as relative risk (RR) with 95 % confidence intervals (CI). Continuous variables were expressed as standardized mean differences (SMD). Main results: Hyaluronic acid gel reduced the intrauterine adhesion scores after miscarriage (SMD -0.68, 95 % CI -1.08～-0.28; p  = 0.0008) and the incidence of postoperative intrauterine adhesions after miscarriage (RR 0.44, 95 % CI 0.29～0.67; p  = 0.0001). Subgroup analysis found that hyaluronic acid gel reduced the incidence of moderate and severe intrauterine adhesions after miscarriage (RR 0.18, 95 % CI: 0.07～0.47; p  = 0.0004), but had no effect on the incidence of mild intrauterine adhesions (RR 0.77, 95 % CI 0.42～1.19; p  = 0.19). Hyaluronic acid gel also improved the pregnancy rate after miscarriage (RR 1.94, 95 % CI 1.46～2.60; p  < 0.00001). Conclusion: Hyaluronic acid gel significantly reduced the incidence of moderate and severe intrauterine adhesions and significantly improved the pregnancy rate after miscarriage.